2020
DOI: 10.1038/s41564-020-0740-y
|View full text |Cite
|
Sign up to set email alerts
|

Exosome mimicry by a HAVCR1–NPC1 pathway of endosomal fusion mediates hepatitis A virus infection

Abstract: Cell-to-cell communication by exosomes controls normal and pathogenic processes 1 , 2 . Viruses can spread in exosomes and thereby avoid immune recognition 3 . While biogenesis, binding, and uptake of exosomes are well-characterized 4 , 5 , delivery of exosome cargo into the cytoplasm is poorly understood 3 . We report that phosphatidylserine receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 58 publications
0
32
0
Order By: Relevance
“…Feng et al identified exosome-like viral particles, which are characterized by incorporating HAV virions into exosomes with a diameter of 50–110 nm, and termed as quasi-enveloped HAV (eHAV) [ 70 , 71 , 72 ]. It was reported that phosphatidylserine receptor HAVCR1 (CD365) and cholesterol transporter NPC1 involve in the transportation of eHAV through clathrin-mediated endocytosis, which is necessary for the membrane fusion and transport of viral RNA from eHAV into the cytoplasm [ 73 , 74 ]. Moreover, host gangliosides are essential endosomal receptors for uncoating and delivery of the viral RNA genome to the cytoplasm of eHAV and naked HAV [ 72 ].…”
Section: Roles Of Exosomes In Nonenveloped Rna Virus Processesmentioning
confidence: 99%
“…Feng et al identified exosome-like viral particles, which are characterized by incorporating HAV virions into exosomes with a diameter of 50–110 nm, and termed as quasi-enveloped HAV (eHAV) [ 70 , 71 , 72 ]. It was reported that phosphatidylserine receptor HAVCR1 (CD365) and cholesterol transporter NPC1 involve in the transportation of eHAV through clathrin-mediated endocytosis, which is necessary for the membrane fusion and transport of viral RNA from eHAV into the cytoplasm [ 73 , 74 ]. Moreover, host gangliosides are essential endosomal receptors for uncoating and delivery of the viral RNA genome to the cytoplasm of eHAV and naked HAV [ 72 ].…”
Section: Roles Of Exosomes In Nonenveloped Rna Virus Processesmentioning
confidence: 99%
“…Whether the protracted low-level RNAemia observed during the late phase of infection is relevant from a pathophysiologic perspective is less clear and might depend on the HAV variant circulating. Although naked HAV virions are expected to be neutralized by HAV antibodies, this assumption might not apply to the more recently described quasi-enveloped HAV particles (3) and capsid-free HAV genomes, which are infectious because the RNA plusstrand orientation enables direct use as messenger RNA (24,25). The host cell entry of both of these variants is mediated by exosomes and relies on distinct host cell factors not used in the same way by naked virions (25).…”
Section: Discussionmentioning
confidence: 99%
“…A third cell-to-cell transmission pathway of HAV has been recently described, based on the delivery of capsid-free RNA genomes which are an abundant cargo of the quasi-enveloped virions [ 53 ]. The quasi-enveloped virions, which are exosomes in nature, carry phosphatidylserine molecules in their membranes, which interact with the extracellular domain of the phosphatidylserine receptor (HAVCR1), previously described as a HAV receptor [ 54 , 55 ], mediating their uptake by clathrin-mediated endocytosis [ 56 ].…”
Section: The Hepatitis a Virus Life Cycle: Atypical Virus–host Interamentioning
confidence: 99%